Nanocellulose: a promising green treasure from food wastes to available food materials. Issue 4 (21st February 2022) - Ma, Tao; Hu, Xinna; Lu, Shuyu; Liao, Xiaojun; Song, Yi; Hu, Xiaosong
Abstract: The synthesis of novel functional materials from abundant food waste resources has great application potentials and ecological benefits. Nanocellulose is a renewable and sustainable polymer that possesses a modifiable surface, excellent mechanical strength, and high aspect ratio, and it is nontoxic. These unique properties garner nanocellulose a promising prospect for multi-various applications including the food industry. This review presents the structural characteristics and advances in the extraction approaches of nanocellulose, with an emphasis in recent progress on the various applications of nanocellulose in the field of food industry. Finally, the environmental and human health issues related to the production of nanocellulose are evaluated. The scheme to extract and produce nanocellulose from food wastes provides a platform for the sustainable utilization of waste biomass. These nanocelluloses exhibit excellent performances in green food packaging materials, emulsion stabilizers, dietary fiber, nutrition delivery and food three-dimensional (3 D) printing hydrogels. To ensure the security and regulatory issues, validated standards to characterize the structure and evaluate its toxicity are still indispensable to achieve the commercialization of nanocellulose in the food industry.